2014
DOI: 10.1172/jci74438
|View full text |Cite
|
Sign up to set email alerts
|

Periostin promotes liver steatosis and hypertriglyceridemia through downregulation of PPARα

Abstract: Periostin neutralizing Ab. The hybridoma cell lines secreting mouse mAb against mouse periostin were generated by Abmart Co., according to the standard hybridoma technique (72). The mouse mAbs were purified by Protein A affinity chromatograph. mAb purity was confirmed by HPLC. The concentrations of the obtained mAbs were measured by Mouse IgG ELISA Quantitation kit (Bethyl Laboratories), following the manufacturer's instructions. The kinetic parameters of the mAbs were determined using a Biacore T100 instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
131
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 72 publications
10
131
2
Order By: Relevance
“…In line with experimental models, hepatic periostin expression and serum periostin levels were increased in NAFLD patients compared with controls [7]. Other authors also reported higher serum periostin levels in patients with acute or chronic hepatitis compared with controls; in the same study, periostin levels were well associated with TGF-b1 and TGF-b2 [9].…”
Section: Periostin In Hepatic Metabolismsupporting
confidence: 62%
See 3 more Smart Citations
“…In line with experimental models, hepatic periostin expression and serum periostin levels were increased in NAFLD patients compared with controls [7]. Other authors also reported higher serum periostin levels in patients with acute or chronic hepatitis compared with controls; in the same study, periostin levels were well associated with TGF-b1 and TGF-b2 [9].…”
Section: Periostin In Hepatic Metabolismsupporting
confidence: 62%
“…A eightfold higher hepatic periostin expression was shown in mice fed a high-fat diet compared with a chow diet [7]. Hepatic periostin was also markedly higher in ob/ob and db/db mice, known models of monogenic obesity and NAFLD, compared to lean controls [7]. Furthermore, overexpression of periostin in the liver of wild-type mice promoted hypertriglyceridemia and hepatic steatosis, possibly through reducing the expression of peroxisome proliferator-activated receptor (PPAR)-a pathway, thereby reducing fatty acid oxidation [7].…”
Section: Periostin In Hepatic Metabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…High‐fat feeding in mice induced Postn mRNA after a relatively short time course of 6 weeks, while the majority of our study participants had chronically established metabolic dysfunction including insulin resistance or type 2 diabetes, which could help explain this apparent discrepancy. In livers, Postn expression is elevated in obese mice and humans, and overexpression of periostin in mouse livers promoted hepatic steatosis and hypertriglyceridemia (Lu et al, 2014). These counteracting processes in liver and AT may explain the limited effects on plasma lipids and glucose metabolism and imply a tissue‐specific regulation and function of periostin.…”
Section: Discussionmentioning
confidence: 99%